Assessing anthropogenic pressures on bird diversity in Nijhum Dwip National Park, Bangladesh (Bangladesh Journal of Zoology, 2025)
Nijhum Dwip National Park is a biodiversity-rich coastal ecosystem that plays a crucial role in preserving a variety of plant and animal species. It is made up of a series of islands, primarily covered by mangroves, tidal forests, and mudflats which serve as vital habitat for birds. A study was conducted on the impacts of anthropogenic activities on birds of Nijhum Dwip National Park from October 2023 to March 2024. Studying the impacts of anthropogenic activities on birds of this area is significant for ensuring the long-term health of bird populations, especially migratory species that rely on the diverse ecosystems of the park. A total of 67 species of birds belonging to 56 genera, 32 families and 13 orders were recorded from Nijhum Dwip National Park. The eight major anthropogenic activities (overfishing, tourism, hunting, deforestation, sound pollution, settlement, agricultural practices, and water pollution) were observed in the study area throughout the study period. Of all the human activities, overfishing caused a severe level (27.88%) of disturbance followed by tourism (21.15%), hunting (18.26%), and sound pollution (14.42%) having a moderate level of disturbance. This study reveals that human disturbances have a severe impact on the habitat, food, breeding behaviour, and survival of birds. The obtained results are significant for the conservation and management efforts since they indicate levels of human disturbances across the habitat. By understanding the threats posed by human activities, we can preserve the habitat of birds and maintain the integrity of the ecosystem which contributes to the broader goals of biodiversity conservation and sustainable development in the region.Bangladesh J. Zool. 53(1): 31-44, 2025